Labour mobility in the enlarged single European market - Dlvik, Jon Erik.; Eldring, Line. (Bingley, U.K. : Emerald, 2016)
The 2004 reunification of Eastern and Western Europe and the subsequent economic crisis caused a surge in intra-European labour mobility and a profound shift in preceding patterns of migration in Europe. While previous decades of European integration brought very modest cross-border flows of labour, the past decade has engendered the largest European movements of labour in modern time mostly from East to West, but eventually also from South to North. In a situation of record high European unemployment, this has sparked controversy about the very notion of free movement, one of the basic foundations of the European Community, and has unleashed heated debates about the conditions, causes, and consequences of large-scale labour migration for receiving as well as sending societies. Against this background, this volume of Comparative Social Research will contribute to improve our understanding of the drivers, mechanisms, and effects of the past decade's surge in cross-border labour mobility and work related migration within Europe.
Introduction: transnational labour mobility - engine for social convergence or divergence in Europe? / Jon Erik Dlvik -- New patterns of labour migration from Central and Eastern Europe and its impact on labour markets and institutions in Norway: reviewing the evidence / Jon Horgen Friberg -- Policy response to emigration from the Baltics: confronting'the European elephant in the room' / Indre Genelyte -- Sectoral variation in consequences of intra-European labour migration: how unions and structural conditions matter / Bjarke Refslund -- A Canadian immigration model for Europe? labour market uncertainty and migration policy in Canada, Germany, and Spain / Guglielmo Meardi, Antonio Marti<U+0301>n Artiles, Axel van den Berg -- Move to work, move to stay? mapping atypical labour migration into Germany / Bettina Wagner, Anke Hassel -- Freer labour markets, more rules? how transnational labour mobility can strengthen collective bargaining / Alexandre Afonso -- East-West mobility and the (re-)regulation of employment in transnational labour markets / Torben Krings -- Locked in inferiority? the positions of Estonian construction workers in the Finnish migrant labour regime / Markku Sippola, Kairit Kall.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Labor; Sociology: work & labour; Labor mobility -- European Union countries